DETERMINATION OF HEARTH POSITION OF A FORTHCOMING STRONG EQ USING GRADIENTS AND PHASE VELOCITIES OF ULF GEOMAGNETIC DISTURBANCES - Kopytenko Yu.A.; Ismaguilov V.S.; Hattori K.; Hayakawa M. (My University, 2006)
Behavior of gradient and phase velocity vectors of ULF (F < 1 Hz) geomagnetic disturbances was investigated for two earthquake (EQ) events in Japan in 2000 (M > 6) and 2003 (M = 5.8) years. The gradient and phase velocity vectors were determined using the data of three high-sensitive three-component magnetic stations situated at a distance ~5 km from each other (magnetic gradientometer). Two gradientometers were installed southeast and southwest of Tokyo at a distance ~150 km from each other. It was found that the gradient and phase velocity values had anomaly changes 3-4 months before the strong EQs. New directions of the gradient vectors took place in the same period - the directions just to the forthcoming EQ epicenter. The directions from the forthcoming EQ epicenter arouse for the phase velocity vectors. We propose to use the gradient and phase velocity vectors of the ULF geomagnetic disturbances as important factors of the short-term prediction of strong earthquakes. © 2006.
Keywords: DIRECTION FINDING; MAGNETIC GRADIENTOMETER; SEISMOGENIC ULF EMISSIONS; SHORT-TERM EARTHQUAKE PREDICTION